Effect of Changing the Parameters of the Multi Jet Fusion (MJF) Process on the Spatial Objects Produced - Maciej CADER; Wojciech KIŃSKI (Problemy Mechatroniki)
This paper describes the principle of operation of Multi Jet Fusion (MFJ) technology in detail. Hybrid strength tests were carried out using an INSTRON 5967 universal testing machine controlled by the Bluehill 3 program and coupled with the ARAMIS measurement system (GOM, Gmbh), enabling the monitoring of deformations in three axes, using a system of high-speed cameras. The results are given of the static tensile test of samples in two printing modes characteristic of the MJF technology – FAST and BALANCE.